PENELITIAN PENGEMBANGAN EKOSISTEM RAWA UNTUK MENDUKUNG PENGEMBANGAN EKONOMI WILAYAH DI KABUPATEN TAPIN - Baparki, Ahmad; Bahrun; Refiana, Fenny (Chlorophyl, 2024)
Development about bog Ecosystem is require to be conducted to support regional economic expansion. This matter is adapted for by Set Of the Land;Ground Map (SPT), assessment of according to farm actual and potential. At agriculture Ecosystem development bog relate is to zomasi pond irrigate, bog draining process, condition biofisik, pre-eminent election varitas, conducting drainage and irrigation irrigation infrastructure lengthenedly walked for another commodity.Fishery development with original typical fish owning high economic value like Tauman, Sepat Siam, Betok dan Sepat Rawa. Ranch development with bog buffalo and duck and also the tourism development about thought nature fishing experienced and river transportation